Identifikasi perubahan fisik rumah masyarakat Samin Blora berdasarkan teori Habraken - Badrut Anggara Putra; Agung Budi Sarjono; Edward Endrianto Pandelaki (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Cultural transformation is one of the Habraken Architectural theories, which involves three categories of change, namely physical, spatial, and cultural. The development of modern culture in the residential area of the Samin community in Blora Regency has an impact on the emergence of physical changes in the shelter. Hence, this study aimed to identify the physical changes and the aspects affecting them. There are six basic aspects in the theory of physical change proposed by Habraken, namely Body & Utensils, Furniture, Partitioning, building elements, roads, and Major Artery. A deductive rationalistic approach and qualitative descriptive methods were used in this study for collecting data through interviews with the Samin community in Blora Regency, for field observations, and analyzing the physical changes of the object. This analysis refers to the concept of changing the cultural structure of Habraken. Consequently, the conclusion showed that the people in Blora still adhere to the teachings of samin. Among the six objects, only two modern materials were used, namely glass and ceramic floors. Moreover, body utensils and building elements were the aspects that mostly influence the changes that occurred.